New Approaches Toward the Hydrogen Production From Formic Acid Dehydrogenation Over Pd-Based Heterogeneous Catalysts - Navlani-García, Miriam; Mori, Kohsuke; Salinas-Torres, David; Kuwahara, Yasutaka; Yamashita, Hiromi (Frontiers in Materials, 2019)
The urgency of finding clean energy sources is nowadays latent and the role of hydrogen in the future energy scenario is well-recognized. However, there are still various barriers that limit the widespread utilization of hydrogen, which are mainly related to its storage and transportation. Chemical hydrogen storage stands out as a suitable alternative to those traditional physical storage methods and formic acid holds tremendous promise within the molecules studied so far. This review summarizes some of the recent approaches considered in our research group for the preparation of efficient catalysts for the production of hydrogen via dehydrogenation of formic acid by using Pd-based heterogeneous catalysts supported on carbon or carbon-containing materials. Several routes were considered to attain efficient catalysts, covering from the optimization of the size and composition of the nanoparticles to the modulation of important features of the support, such as the porous texture and nitrogen doping level.